Sustained usage of bioethanol cookstoves shown in an urban Nigerian city via new SUMs algorithm - Northcross, Amanda; Shupler, Matt; Alexander, Donee; Olamijulo, John; Ibigbami, Temitope; Ana, Godson; Ojengbede, Oladosu; Olopade, Christopher O. (Energy for sustainable development, 2016)
An unbiased assessment of cooking patterns during a cookstove intervention can provide strong evidence for sustained usage of a cookstove among the target population. A bioethanol cookstove was used as an intervention within a randomized controlled trial being conducted in Ibadan, Nigeria to assess the ability of a clean stove to improve birth outcomes. Sustained usage of the intervention was quantified using a newly developed method of analyzing cooking patterns based on time integrated temperature data from Stove Use Monitors (SUMs) installed on household cookstoves. The method accounts for household level variations in ambient temperatures. We report a significant decline of traditional kerosene stove usage, 84% of women in the Bioethanol arm giving away their kerosene stove before the conclusion of the study (56% within the first month of enrollment), suggesting the bioethanol stove replaced the kerosene stove. This is the first study to objectively evaluate a liquid-to-liquid fuel substitution. •a liquid-to-liquid fuel cookstove substitution resulted in very limited stove-stacking•participants using the bioethanol cookstove used the stove consistently•cooking pattern analysis using data from Stove Use Monitors accounted for household level variations in ambient temperatures